A 4D ultrasound real-time tracking system for external beam radiotherapy of upper abdominal lesions under breath-hold - Sihono, Dwi Seno Kuncoro; Vogel, Lena; Weiß, Christel; Thölking, Johannes; Wenz, Frederik; Lohr, Frank; Boda-Heggemann, Judit; Wertz, Hansjörg (Strahlentherapie und Onkologie, 2017)
Background and purpose: To evaluate a novel four-dimensional (4D) ultrasound (US) tracking system for external beam radiotherapy of upper abdominal lesions under computer-controlled deep-inspiration breath-hold (DIBH). Materials and methods: The tracking accuracy of the research 4D US system was evaluated using two motion phantoms programmed with sinusoidal and breathing patterns to simulate free breathing and DIBH. Clinical performance was evaluated with five healthy volunteers. US datasets were acquired in computer-controlled DIBH with varying angular scanning angles. Tracked structures were renal pelvis (spherical structure) and portal/liver vein branches (non-spherical structure). An external marker was attached to the surface of both phantoms and volunteers as a secondary object to be tracked by an infrared camera for comparison. Results: Phantom measurements showed increased accuracy of US tracking with decreasing scanning range/increasing scanning frequency. The probability of lost tracking was higher for small scanning ranges (43.09% for 10° and 13.54% for 20°).The tracking success rates in healthy volunteers during DIBH were 93.24 and 89.86% for renal pelvis and portal vein branches, respectively. There was a strong correlation between marker motion and US tracking for the majority of analyzed breath-holds: 84.06 and 88.41% of renal pelvis target results and 82.26 and 91.94% of liver vein target results in anteroposterior and superoinferior directions, respectively; Pearson’s correlation coefficient was between 0.71 and 0.99. Conclusion: The US system showed a good tracking performance in 4D motion phantoms. The tracking capability of surrogate structures for upper abdominal lesions in DIBH fulfills clinical requirements. Further investigation in a larger cohort of patients is underway.